TINJAUAN YURIDIS PERTANGGUNG JAWABAN PERSEROAN TERBATAS DALAM CORPORATE SOCIAL RESPONSIBILITY TERHADAP KERUSAKAN LINGKUNGAN HIDUP - frinda susanto (to-ra, 2021)
Article 74 of Law 40 of 2007 concerning Limited Liability Companies, stipulates that: "it is mandatory to carry out corporate social responsibility for companies that carry out their business activities in fields and / or related to natural resources." However, this regulation does not clearly explain what kind ofactivities corporate social responsibility a limited liability company should undertake. Corporate social responsibility has the aim of improving the welfare of the surrounding community who live and depend on the surrounding environment where the limited liability company runs its business. Legal certainty of the obligation for companies to carry out corporate social responsibility and the obligation to protect the surrounding environment already exists, but the benefits of these laws and regulations are still minimal considering the many forms of violations committed by limited liability companies. sanctions for companies that do not implement corporate social responsibility are clearly displayed in the statutory regulations, but the facts based on the research conducted by the author feel that the imposition of these sanctions has not been implemented properly. Keywords: corporate social responsibility, limited liability company, regulations